Isolated central nervous system familial hemophagocytic lymphohistiocytosis (fHLH) presenting as a mimic of demyelination in children. (April 2022) - Parida, Amitav; Abdel-Mannan, Omar; Mankad, Kshitij; Foster, Katharine; Ramdas, Sithara; Ram, Dipak; Eleftheriou, Despina; Hemingway, Cheryl; Hacohen, Yael; Wassmer, Evangeline
Isolated central nervous system (CNS) presentations of haemophagocytic lymphohistiocytosis (HLH), traditionally a systemic inflammatory condition, have been reported in adults and children. We identified nine patients with a diagnosis of isolated CNS familial hemophagocytic lymphohistiocytosis (fHLH) with symptom onset <18 years of age, and one asymptomatic sibling. Children with atypical chronic/recurrent CNS inflammation should be considered for immunological and genetic panel testing for fHLH even in the absence of any systemic inflammatory features. Despite haematopoietic stem cell transplantation (HSCT) being a mainstay of treatment, treatment failure and high morbidity and mortality post-HSCT suggest that alternative immune therapies may be worth considering.